2017
DOI: 10.18632/oncotarget.14956
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum chemerin levels in patients with non-small cell lung cancer

Abstract: Chemerin plays an important role in adipogenesis and chemotaxis of the innate immune system. The aim of this study was to explore the significance and prognostic value of serum chemerin levels in patients with non-small cell lung cancer (NSCLC). Serum specimens from 189 NSCLC patients and 120 healthy controls were collected. The levels of serum chemerin were measured by sandwich enzyme-linked immunosorbent assay (ELISA). The serum chemerin levels were significantly elevated in NSCLC patients compared with heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 19 publications
3
39
0
1
Order By: Relevance
“…When compared to the adjacent Barrett’s tissue, the malignant tissues of esophageal adenocarcinoma were reported to have high chemerin expression, 49 , 50 which confirmed an association between overexpression of chemerin and chemR23 and a more invasive esophageal squamous cell carcinoma. Recently, Xu et al 51 reported that chemerin expression in serum may be considered as a serum biomarker for diagnosis and prognosis in non-small-cell lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the adjacent Barrett’s tissue, the malignant tissues of esophageal adenocarcinoma were reported to have high chemerin expression, 49 , 50 which confirmed an association between overexpression of chemerin and chemR23 and a more invasive esophageal squamous cell carcinoma. Recently, Xu et al 51 reported that chemerin expression in serum may be considered as a serum biomarker for diagnosis and prognosis in non-small-cell lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…This adipokine is involved in metabolism and immune reactions. Recently, the potential role of chemerin in cancerogenesis was described [37,38]. Higher chemerin levels were observed in non-small cell lung cancer patients compared with healthy controls and were associated with advanced TNM stage [37].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Recently, the potential role of chemerin in cancerogenesis was described [37,38]. Higher chemerin levels were observed in non-small cell lung cancer patients compared with healthy controls and were associated with advanced TNM stage [37]. Elevated serum levels of chemerin were also determined in gastric cancer and colorectal cancer patients [38].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Although the treatment of lung cancer has made great breakthroughs in recent decades, traditional chemotherapeutic drugs lacked specific targeting specificity for NSCLC, or had toxic side effects on patients and limited efficacy [7]. The result of the patients' long-term survival did not show significant improvements [8,9]. Therefore, it was necessary and urgent to explore new therapeutic targets for NSCLC.…”
Section: Introductionmentioning
confidence: 99%